2018
DOI: 10.1016/j.celrep.2017.12.073
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Type Specificity of Callosally Evoked Excitation and Feedforward Inhibition in the Prefrontal Cortex

Abstract: SUMMARY Excitation and inhibition are highly specific in the cortex, with distinct synaptic connections made onto subtypes of projection neurons. The functional consequences of this selective connectivity depend on both synaptic strength and the intrinsic properties of targeted neurons but remain poorly understood. Here, we examine responses to callosal inputs at cortico-cortical (CC) and cortico-thalamic (CT) neurons in layer 5 of mouse prelimbic prefrontal cortex (PFC). We find callosally evoked excitation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
94
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 93 publications
(153 reference statements)
19
94
1
Order By: Relevance
“…VM inputs activate NDNF+ cells, which subsequently mediate thalamus-evoked inhibition of the local network. We previously found that PT cells receive much stronger inhibition from PV+ and SOM+ cells (Anastasiades et al, 2018a). Here we find NDNF+ cells also make stronger connections onto PT cells, suggesting this is a general property.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…VM inputs activate NDNF+ cells, which subsequently mediate thalamus-evoked inhibition of the local network. We previously found that PT cells receive much stronger inhibition from PV+ and SOM+ cells (Anastasiades et al, 2018a). Here we find NDNF+ cells also make stronger connections onto PT cells, suggesting this is a general property.…”
Section: Discussionsupporting
confidence: 71%
“…S4). We then injected AAV-DIO-ChR2-mCherry into the PFC and recorded light-evoked IPSCs from L2/3 interneurons or PYRs in the presence of TTX and 4-AP (Anastasiades et al, 2018a;Petreanu et al, 2009) (Fig. 4A-B).…”
Section: Vip+ and Ndnf+ Interneurons Participate In Distinct Output Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Coherent, synchronous oscillations between the vHIP and the mPFC underlie working memory tasks in rats (Gordon, 2011). Entrainment of these oscillations occurs in the first postnatal week (Brockmann et al, 2013) and is driven by monosynaptic glutamatergic projections from pyramidal neurons of the ventral CA1 and subiculum to pyramidal neurons and GABAergic interneurons in the IL and PL subregions of the mPFC (Anastasiades et al, 2018;Dégenètais et al, 2003;Dembrow et al, 2010;Thierry et al, 2000). Despite the wealth of information linking this projection to neuropsychiatric disorders (Li et al, 2015), little is known about the synaptic and cellular bases of this long-range projection.…”
Section: Discussionmentioning
confidence: 99%